Design and testing of communication materials for a breastfeeding social media marketing campaign: Breastfeed4Ghana. (March 2020) - Aryeetey, R; Lasisi, O; Hromi-Fiedler, A; Carroll, G; Pérez-Escamilla, R; Harding, K
Breastfeed4Ghana was a social media-based campaign implemented to address identified gaps in the protection, promotion, and support of breastfeeding in Ghana. This paper describes the process of campaign materials development and testing to ensure their cultural and content appropriateness. The 60 campaign materials, each consisting of an image and text message, underwent a process of creation, testing, revision, and finalization. Existing research evidence and infant and young child feeding communication tools that were culturally relevant for Ghana were used to develop the materials. All materials were tested and finalized through an iterative process that incorporated input from six focus group discussions (FGDs) with mothers, and content and technical experts. The materials were revised to ensure scientific accuracy, understandability, and cultural appropriateness of the messages, as well as alignment of the messages with the images. Finalized materials were reviewed and approved by the Ghana Food and Drugs Authority. Analysis for this paper involved summarizing and categorizing the types and sources of input as well as the research team's responses to the input received. The 60 campaign materials received a total of 132 inputs. Most inputs came from FGDs (78.4%); and most inputs were on the campaign material images. The evidence-informed process of materials creation, use of multiple input sources, and a broad-based iterative process allowed the creation of 60 evidence-based and culturally appropriate materials for a breastfeeding social media campaign in Ghana. This paper could serve as a guide for other social media campaign efforts looking to develop culturally appropriate materials.